Strategi Digitalisasi Promosi UMKM Rengginang Melalui Google Maps dalam Meningkatkan Perekonomian Lokal : (Studi Kasus : Desa Pahang, Kabupaten Batubara) - Imsar Imsar; Adisty Aulia Zahra; Elvira Andriyani; Popi Dea Ananda; Salsabila Sofiya Wardani (BADAN PENERBIT STIEPARI PRESS, 2026)
This study discusses the digitalization strategy for promoting small and medium enterprises (SMEs) producing rengginang in Pahang Village, Batubara Regency, through the use of the Google Maps platform to enhance the local economy. The main objective of this research is to understand how digital promotion can expand market reach, strengthen business branding, and improve community welfare. This research employs a qualitative approach using interviews, observations, and documentation with local SME actors. The results show that using Google Maps significantly helps rengginang SMEs broaden their marketing reach, increase business visibility, and build consumer trust through reviews and digital location features. In addition to boosting sales, digitalization also stimulates local economic growth by creating job opportunities and strengthening community engagement in the digital economy. Therefore, a Google Maps–based digitalization strategy can serve as an effective solution for SMEs to face modern economic challenges and strengthen regional economic resilience sustainably.